Passive remote sensing of aerosol layer height using near‐UV multiangle polarization measurements. Issue 16 (25th August 2016) - Wu, Lianghai; Hasekamp, Otto; van Diedenhoven, Bastiaan; Cairns, Brian; Yorks, John E.; Chowdhary, Jacek
Abstract: We demonstrate that multiangle polarization measurements in the near‐UV and blue part of the spectrum are very well suited for passive remote sensing of aerosol layer height. For this purpose we use simulated measurements with different setups (different wavelength ranges, with and without polarization, different polarimetric accuracies) as well as airborne measurements from the Research Scanning Polarimeter (RSP) obtained over the continental USA. We find good agreement of the retrieved aerosol layer height from RSP with measurements from the Cloud Physics Lidar showing a mean absolute difference of less than 1 km. Furthermore, we found that the information on aerosol layer height is provided for large part by the multiangle polarization measurements with high accuracy rather than the multiangle intensity measurements. The information on aerosol layer height is significantly decreased when the shortest RSP wavelength (410 nm) is excluded from the retrieval and is virtually absent when 550 nm is used as shortest wavelength. Key Point: We find good agreement of the retrieved aerosol layer height from RSP with measurements from the Cloud Physics Lidar